Eksekusi Mati Dalam Perspektif Hukum Pidana Internasional dan Penerapannya di Indonesia - Fikrie, Safina Nabila; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article examines death executions from the perspective of international criminal law and its application in Indonesia considering that there are still clashes or conflicting norms in implementing them in Indonesia. The research method used is the Normative Juridical research method. Normative Juridical Research is a legal research method carried out by examining library materials or mere secondary materials. This research approach is a statutory and case approach. This approach is carried out by examining laws and cases related to the legal issues being studied. In this case the author refers to Law Number 1 of 2023 concerning the Criminal Code, Declaration of Human Rights, and the International Covenant on Civil and Political Rights (ICCPR). The research results show that the implementation of death executions in Indonesia faces complex challenges, especially due to international pressure related to human rights. Many countries and international organizations have criticized the death penalty as a violation of the right to life, including Amnesty International and Human Rights Watch. Indonesia's commitment to international treaties, such as the International Covenant on Civil and Political Rights (ICCPR), adds to the dilemma of balancing international compliance with national law. Differences between national laws that allow the death penalty for serious crimes, such as narcotics and terrorism, and international standards that encourage restrictions on the death penalty also complicate the situation.